From a Molecular 2Fe‐2Se Precursor to a Highly Efficient Iron Diselenide Electrocatalyst for Overall Water Splitting. Issue 35 (19th July 2017) - Panda, Chakadola; Menezes, Prashanth W.; Walter, Carsten; Yao, Shenglai; Miehlich, Matthias E.; Gutkin, Vitaly; Meyer, Karsten; Driess, Matthias
Abstract: A highly active FeSe2 electrocatalyst for durable overall water splitting was prepared from a molecular 2Fe‐2Se precursor. The as‐synthesized FeSe2 was electrophoretically deposited on nickel foam and applied to the oxygen and hydrogen evolution reactions (OER and HER, respectively) in alkaline media. When used as an oxygen‐evolution electrode, a low 245 mV overpotential was achieved at a current density of 10 mA cm −2, representing outstanding catalytic activity and stability because of Fe(OH)2 /FeOOH active sites formed at the surface of FeSe2 . Remarkably, the system is also favorable for the HER. Moreover, an overall water‐splitting setup was fabricated using a two‐electrode cell, which displayed a low cell voltage and high stability. In summary, the first iron selenide material is reported that can be used as a bifunctional electrocatalyst for the OER and HER, as well as overall water splitting. Abstract : Bridging the gap : A highly active iron diselenide electrocatalyst was prepared at low temperature from a bioinspired 2Fe‐2Se molecular complex (Dep = diethylphenyl). The catalyst was applied to bifunctional oxygen and hydrogen evolution reactions, as well as overall water splitting. The nature of active sites and structure–activity relationships of the electrocatalyst were uncovered.